Peran Iklim Integritas dalam Menjelaskan Pengaruh Kepemimpinan Etis terhadap Pelanggaran Integritas di Sektor Publik - Jhon Kenedy Simarmata; Warji Permana; Warsito Kawedar (Politeknik Ganesha Medan, 2025)
Government has recently paid more attention to the integrity of civil servants in providing public services. This is an effort to create a service environment that is free from corruption and able to provide excellent service to the public. Therefore, this study attempts to explain the effect of ethical leadership on integrity violations through the integrity climate in public sector organizations. This research was conducted at one of the institutions in Indonesia that has units spread across all provinces in Indonesia. Using a systematic random sampling design, 442 employees were selected who were then asked to fill out a questionnaire. Total of 393 employees were willing to fill out the research questionnaire which was then processed for analysis. PLS-SEM is used for multivariate analysis and data processed using the SmartPLS 3 application. The results of the analysis show that integrity climate is statistically proven mediating the effect of ethical leadership on integrity violations. These results provide empirical support for the Social Learning Theory which explains that individual behavior is the result of learning from their environment. To mitigate integrity violations in organizations, leaders are expected to be role models of ethical behavior to their subordinates, as well as building a integrity climate in organization.